COVID-19 and Thromboinflammation: Is There a Role for Statins? (Clinics, 2021)
The novel coronavirus disease (COVID-19) showed increased morbidity and mortality rates and worse prognosis in individuals with underlying chronic diseases, especially cardiovascular disease and its risk factors, such as hypertension, diabetes, and obesity. There is also evidence of possible links among COVID-19, myocardial infarction, and stroke. Emerging evidence suggests a pro-inflammatory milieu and hypercoagulable state in patients with this infection. Despite anticoagulation, a large proportion of patients requiring intensive care may develop life-threatening thrombotic complications. Indeed, the levels of some markers of hemostatic activation, such as D-dimer, are commonly elevated in COVID-19, indicating potential risk of deep vein thrombosis and pulmonary thromboembolism. In this review, we critically examine and discuss aspects of hypercoagulability and inflammation in COVID-19 and the possible benefits of statins in this scenario, with emphasis on their underlying molecular mechanisms. Moreover, we present recommendations on the use of antiviral drugs in combination with statins.